Implementation of Independent Curriculum for Rural Schools from a Constructivism Perspective - Stenly, Stenly; Ndona, Yakobus; Gultom, Ibrahim (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This study examines the independent curriculum for rural schools through a constructivist perspective. This study uses qualitative techniques with literature evaluation (Library Research). The purpose of this study is to investigate the implementation of the independent curriculum in rural schools through a constructivist perspective. The independent curriculum allows schools to develop contextual and relevant learning for the needs of their students, especially in rural areas with unique problems. The constructivist approach to learning emphasizes students' active relationship with their environment, allowing them to construct knowledge from real-world experiences. This study uses qualitative methodology with a case study approach in rural schools. The results of the study indicate that although the adoption of the independent curriculum in rural schools has limitations such as limited resources and access to technology, it has great promise to produce relevant and meaningful learning through a constructivist approach. This study concludes that the independent curriculum can be maximized in rural schools by adapting it to local conditions and improving teacher competency in implementing a constructivist learning approach.